What’s hiding under your covers? Inorganic metaphors by Katalin Ladik - Roland, Orcsik (Anafora, 2022)
The paper will present the art of one of the most interesting authors of Hungarian literature, Katalin Ladik – from the aspect of creating the inorganic metaphor. The Voivodinian and Ex-Yugoslavian neoavantgarde scene will be discussed, especially the authors and relationships of the magazine Új Symposion from Novi Sad (Újvidék). The parallel with the Hungarian experimental art is important as well. The paper analyses the private mythology, autonomous artworks, and mystical anarchy of Ladik from the aspect of perversion, “not hygienic” and transgression. In conclusion, the paper will analyse the works of some young ontemporary authors, in whose works the explosion of trope figures excites similar vibrations as in Ladik’s works.